1995
DOI: 10.1111/j.1348-0421.1995.tb02237.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Porphyromonas gingivalis ATCC 33277 Vesicle on Adherence of Streptococcus mutans OMZ 70 to the Experimental Pellicle

Abstract: The vesicles of Porphyromonas gingivalis ATCC 33277 strongly aggregated Streptococcus cricetus, S. rattus, and S. mutans, but poorly aggregated S. sobrinus. The adherence of S. mutans OMZ 70 to hydroxyapatite (HA) coated with whole saliva was increased in parallel with the quantity of the vesicles. The significant increase of adherence of S. mutans OMZ 70 by the vesicles was also observed on the HA coated with parotid saliva, submandibular saliva, serum, and type I collagen. These findings suggest that the ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Since the BspA protein belongs to the LRR domain family as well as the Big_2 domain family, involved in receptor-ligand recognition via protein-protein interactions, it is possible that BspA interacts with a specific epithelial cell surface receptor for adherence and invasion. Previous studies have shown that P. gingivalis OMVs are potent activators of adhesion and aggregation (15,16) for other gram-positive bacteria. Our investigations of the interactions between P. gingivalis and T. forsythia have shown that the attachment abilities of T. forsythia ATCC 43037 and its BspA mutant were increased in the presence of P. gingivalis vesicles, supporting the notion that synergy exists between these two species with respect to adherence and colonization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the BspA protein belongs to the LRR domain family as well as the Big_2 domain family, involved in receptor-ligand recognition via protein-protein interactions, it is possible that BspA interacts with a specific epithelial cell surface receptor for adherence and invasion. Previous studies have shown that P. gingivalis OMVs are potent activators of adhesion and aggregation (15,16) for other gram-positive bacteria. Our investigations of the interactions between P. gingivalis and T. forsythia have shown that the attachment abilities of T. forsythia ATCC 43037 and its BspA mutant were increased in the presence of P. gingivalis vesicles, supporting the notion that synergy exists between these two species with respect to adherence and colonization.…”
Section: Discussionmentioning
confidence: 99%
“…The P. gingivalis OMVs released into the environment are thought to play important roles in periodontal disease by serving as vehicles for toxin and enzyme spreading as well as being involved in the adherence and aggregation of bacteria (1,6,20). P. gingivalis OMVs have also been shown to be potent activators of adhesion (16) and aggregation for other oral bacteria (15). P. gingivalis OMVs have been shown to aggregate host platelets (33) as well as to invade epithelial cells in vitro (13,41).…”
mentioning
confidence: 99%
“…Its fimbriae have been shown to interact with epithelial cells (15), cultured human fibroblasts (20), and saliva-coated hydroxyapatite beads (2,32), while its vesicles have been shown to interact with collagen-coated hydroxyapatite beads (32). Further, in studies to determine which of the surface components of P. gingivalis interact with grampositive bacteria, its fimbriae have been reported to interact with A. viscosus (12) and S. gordonii (24); its vesicles have been reported to interact with A. naeslundii (8), A. viscosus (13), and S. mutans (17); and its hemagglutinin has been reported to interact with A. viscosus (34).…”
mentioning
confidence: 99%
“…In order to cause infection, it is necessary for P. gingivalis to attach to tooth surfaces, subgingival epithelium, or early colonizing gram-positive bacteria; this step constitutes the initial stage of colonization in periodontal pockets (38). In addition, the bacterium has been reported to interact with a variety of other oral gram-positive bacteria (19), including Actinomyces naeslundii (36,43), Actinomyces viscosus (9,12,26,27,36), Streptococcus gordonii (23), Streptococcus mutans (17), Streptococcus oralis (29), and Streptococcus sanguis (39); these interactions are considered to play a vital role in the colonization of P. gingivalis in the oral cavity.…”
mentioning
confidence: 99%
“…P. gingivalis possesses several components as adhesins on the cell surface, such as FimA fimbriae and Mfa1 fimbriae (2,6,12,14,17,23,25), vesicles (10,15,19,31), hemagglutinin (24), and Arg-and Lys-specific cysteine proteinases (1). Interactions between the following P. gingivalis cell surface components and oral grampositive bacteria have been documented: (i) FimA fimbriae and Actinomyces viscosus (12), (ii) FimA and Mfa1 fimbriae and Streptococcus gordonii (6,23), (iii) Arg-and Lys-specific cysteine proteinases and A. viscosus (1), and (iv) vesicles and Actinomyces naeslundii (10), A. viscosus (15,31), and Streptococcus mutans (19). Additionally, P. gingivalis FimA fimbriae have been shown to interact with epithelial cells (17), cultured human fibroblasts (14), and salivary proteins (2), which indicates that P. gingivalis FimA fimbriae play an important role as a main adhesive component in bacterial colonization.…”
mentioning
confidence: 99%